#22 Measure Your Calibre

Geometry Level 3

We can express tan 4 x \tan 4x in terms of tan x \tan x as tan ( 4 x ) = a tan x ( 1 tan 2 x ) m + b tan 4 x + k tan 2 x {\tan(4x)= \dfrac{a\tan x (1-\tan^2x)}{m+b\tan^4x+k\tan^2x}} .

Find the sum of constants a + b + k + m a+b+k+m .


Check your Calibre


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Viki Zeta
Mar 14, 2017

tan ( 2 y ) = 2 tan y 1 tan 2 y y = 2 x tan ( 4 x ) = 2 tan ( 2 x ) 1 tan 2 ( 2 x ) = 2 × ( 2 tan x 1 tan 2 x ) 1 ( 2 tan x 1 tan 2 x ) 2 = 4 tan x 1 tan 2 x × 1 ( 1 tan 2 x ) 2 4 tan 2 x ( 1 tan 2 x ) 2 = 4 tan x 1 tan 2 x × ( 1 tan 2 x ) 2 ( 1 tan 2 x ) 2 4 tan 2 x = 4 tan x ( 1 tan 2 x ) ( 1 tan 2 x ) 2 4 tan 2 x cancel out ( 1 tan 2 x ) 2 = 4 tan x ( 1 tan 2 x ) 1 2 t a n 2 x + tan 4 x 4 tan 2 x = 4 tan x ( 1 tan 2 x ) 1 6 t a n 2 x + tan 4 x = 4 tan x ( 1 tan 2 x ) 1 + 1 tan 4 x 6 tan 2 x = 4 tan x ( 1 tan 2 x ) 1 + 1 tan 4 x 6 tan 2 x a + b + k + m = 4 + 1 + 1 6 = 6 6 = 0 \tan(2y) = \dfrac{2\tan y}{1 -\tan^2y} \\ \boxed{y = 2x} \\ \tan(4x) = \dfrac{2\tan(2x)}{1-\tan^2(2x)} \\ = \dfrac{2 \times \left( \dfrac{2\tan x}{1 -\tan^2x} \right)}{ 1 - \left( \dfrac{2\tan x}{1 -\tan^2x} \right)^2} \\ = \dfrac{4\tan x}{1 - \tan^2x} \times \dfrac{1}{\dfrac{(1 - \tan^2x)^2 - 4\tan^2x}{(1 - \tan^2x)^2}} \\ = \dfrac{4\tan x}{1 - \tan^2x} \times \dfrac{(1 - \tan^2x)^2}{(1 - \tan^2x)^2 - 4\tan^2x} \\ = \dfrac{4\tan x (1 - \tan^2x)}{(1 - \tan^2x)^2 - 4\tan^2x} ~~ \boxed{\text{cancel out }(1 - \tan^2x)^2} \\ = \dfrac{4\tan x(1-\tan^2x)}{1 - 2tan^2x + \tan^4x - 4\tan^2x} \\ = \dfrac{4\tan x(1-\tan^2x)}{1 - 6tan^2x + \tan^4x} \\ = \dfrac{4\tan x(1-\tan^2x)}{1 + 1\tan^4x - 6\tan^2x} \\ = \dfrac{\color{#D61F06}{4} \color{#333333}{} \tan x(1-\tan^2x)}{\color{#3D99F6}{1} \color{#333333}{} + \color{#E81990}{1} \color{#333333}{} \tan^4x - \color{#20A900}{6} \color{#333333}{} \tan^2x} \\ \boxed{\therefore \color{#D61F06}{a} + \color{#3D99F6}{b} + \color{#E81990}{k} + \color{#20A900}{m} \color{#333333}{= } \color{#D61F06}{4} + \color{#3D99F6}{1} + \color{#E81990}{1} - \color{#20A900}{6} \color{#333333}{}= 6 - 6 = 0}

Tapas Mazumdar
Mar 18, 2017

tan ( 4 x ) = 2 tan ( 2 x ) 1 tan 2 ( 2 x ) = 2 ( 2 tan x 1 tan 2 x ) 1 ( 2 tan x 1 tan 2 x ) 2 = 4 tan x 1 tan 2 x 1 4 tan 2 x ( 1 tan 2 x ) 2 = 4 tan x ( 1 tan 2 x ) ( 1 tan 2 x ) 2 4 tan 2 x = 4 tan x ( 1 tan 2 x ) 1 + tan 4 x 6 tan 2 x a + b + k + m = 4 + 1 + ( 6 ) + 1 = 0 \begin{aligned} \tan(4x) &= \dfrac{2 \tan(2x)}{1 - \tan^2(2x)} \\ &= \dfrac{2 \left( \frac{2 \tan x}{1- \tan^2 x} \right)}{1 - {\left( \frac{2 \tan x}{1- \tan^2 x} \right)}^2 } \\ &= \dfrac{ \frac{4 \tan x}{1- \tan^2 x} }{ 1 - \frac{4 \tan^2 x}{ {(1-\tan^2 x)}^2 } } \\ &= \dfrac{4 \tan x (1 - \tan^2 x)}{ {(1-\tan^2 x)}^2 - 4 \tan^2 x } \\ &= \dfrac{4 \tan x (1 - \tan^2 x)}{1 + \tan^4 x - 6 \tan^2 x} \end{aligned} \\ \implies a+b+k+m = 4+1+(-6)+1 = \boxed{0}

Miki Moningkai
May 28, 2018

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...